MODELING OF OPERATION MODES OF SHIP POWER PLANT OF COMBINED PROPULSION COMPLEX WITH CONTROL SYSTEM BASED ON ELECTRONIC CONTROLLERS - E. A. Yushkov (National Technical University "Kharkiv Polytechnic Institute", 2016)
Purpose. Designing of diagrams to optimize mathematic model of the ship power plant (SPP) combined propulsion complexes (CPC) for decreasing operational loss and increasing fuel efficiency with simultaneous load limiting on medium revolutions diesel generator (MRDG) by criterion reducing of wear and increasing operation time between repairs. Methodology. After analyzing of ship power plant modes of CPC proposed diagrams to optimize mathematic model of the above mentioned complex. The model based on using of electronic controllers in automatic regulation and control systems for diesel and thruster which allow to actualize more complicated control algorithm with viewpoint of increasing working efficiency of ship power plant at normal and emergency modes. Results. Determined suitability of comparative computer modeling in MatLab Simulink for building of imitation model objects based on it block diagrams and mathematic descriptions. Actualized diagrams to optimize mathematic model of the ship’s power plant (SPP) combined propulsion complexes (CPC) with Azipod system in MatLab Simulink software package Ships_CPC for decreasing operational loss and increasing fuel efficiency with simultaneous load limiting on medium revolutions diesel generator (MRDG) by criterion reducing of wear and increasing operation time between repairs. The function blocks of proposed complex are the main structural units which allow to investigate it normal and emergency modes. Originality. This model represents a set of functional blocks of the components SPP CPC, built on the principle of «input-output». For example, the function boxes outputs of PID-regulators of MRDG depends from set excitation voltage and rotating frequency that in turn depends from power-station load and respond that is a ship moving or dynamically positioning, and come on input (inputs) of thruster rotating frequency PID-regulator models. Practical value. The results of researches planned to use in creation of software package Ships_CPC, in Mat Lab/Simulink was developed under the state budget project «Concepts, technologies and ways of improving ship plants combined propulsion complexes» at the Department of Electromechanics and Electrical Engineering of National University «Odessa Maritime Academy» (State registration number 0114u000340).